Dependence on seagrass fisheries governed by household income and adaptive capacity - Richard Unsworth (Ocean and Coastal Management, 2022)
Seagrass meadows, like other tropical coastal ecosystems, are highly productive and sustain millions of people worldwide. However, the factors that govern the use of seagrass as a fishing habitat over other habitats are largely unknown, especially at the household scale. Using socioeconomic factors from 147 villages across four countries within the Indo-Pacific, we examined the drivers of household dependence on seagrass. We revealed that seagrass was the most common habitat used for fishing across villages in all the countries studied, being preferred over other habitats for reliability. Using structural equation modelling, we exposed how household income and adaptive capacity appears to govern dependence on seagrass. Poorer households were less likely to own motorboats and dependent on seagrass as they were unable to fish elsewhere, whereas wealthier households were more likely to invest in certain fishing gears that incentivised them to use seagrass habitats due to high rewards and low effort requirements. Our findings accentuate the complexity of seagrass social-ecological systems and the need for empirical household scale data for effective management. Safeguarding seagrass is vital to ensure that vulnerable households have equitable and equal access to the resource, addressing ocean recovery and ensuring sustainable coastal communities.